1950
DOI: 10.1021/ja01163a010
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Sulfones. The Condensation of Ethyl Oxalate with Arylmethyl Sulfones

Abstract: We have undertaken the preparation of thiophene-l-dioxides in order to study the attack of free radicals on a vinyl sulfone group (-CH= CH-SOz-) contained in a ring. We are also interested in the reactivity of these thiophene-ldioxides as dienes in the Diels-Alder reaction. This paper will describe the condensation of ethyl oxalate with arylmethyl sulfones (R = 0-naphthyl, phenyl, p-chlorophenyl) to give 2,5-diaryl-3,4 -dihydroxythiophene -1 -dioxides (I). The method is outlined below. Na+OET@ R-CHa-SOz--CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1976
1976
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Prior to some chemical, photophysical and structural studies on the π-extended thionaphthyl systems ( 5) and ( 6), the preparation of reference persulfurated benzene-cored asterisks (3) [8] and (4) [9] was achieved according to known literature methods. The reference thiomethylated naphthalene regioisomers (1) [23] and (2) [24] were also synthesized (see Supporting Information), according to common procedures for methylating aromatic thiols. Thus, 1-naphthalenethiol reacted with an excess of iodomethane (potential carcinogen!)…”
Section: Synthesismentioning
confidence: 99%
“…Prior to some chemical, photophysical and structural studies on the π-extended thionaphthyl systems ( 5) and ( 6), the preparation of reference persulfurated benzene-cored asterisks (3) [8] and (4) [9] was achieved according to known literature methods. The reference thiomethylated naphthalene regioisomers (1) [23] and (2) [24] were also synthesized (see Supporting Information), according to common procedures for methylating aromatic thiols. Thus, 1-naphthalenethiol reacted with an excess of iodomethane (potential carcinogen!)…”
Section: Synthesismentioning
confidence: 99%
“…The treatment of thieno[2,3-b]quinoxaline-2-carbamide 21 with sodium nitrite in acetic acid afforded the corresponding 1,2,3-triazino[4',5':4,5]thieno[2,3-b]quinoxalinone 76, followed by the thiolation using phosphorus pentasulfide and by the chlorination using phosphorus oxychloride to give the corresponding 4-thio and 4-chloro-1,2,3-triazino compounds 77a,b, respectively. Furthermore, hydrazinolysis of the chloride 77b with hydrazine hydrate afforded the 4-hydrazino derivative 78 which was used as a starting material to prepare 1,2,3-triazolo[4",3":1',6'] [1,2,3]triazino [4',5':4,5] thieno[2,3-b]quinoxalines 79a,b [37,38] (Scheme 33).…”
Section: Reviewmentioning
confidence: 99%
“…The "history of thienoquinoxalines" actually began in 1950 with the synthesis of 1,3-dihydro-1,3-diphenylthieno [3,4-b]quinoxaline-2,2-dioxide by Overberger et al [1]. The fusion of quinoxalines with the thiophene ring was expected to yield seven isomers of thienoquinoxalines, such as thieno [2,3- The literature survey revealed that only three isomers of thienoquinoxalines 1a, 1b, and 3a are known.…”
Section: Introductionmentioning
confidence: 99%
“…Neben Benzylchlorid, das mittels Na}:) in Ausbeuten von 80-90% in Dibenzylsulfid uberfuhrt werden konnte [29], [30], wurden zahlreiche mono-und diphenylsubstituierte Benzylhalogenide in ihrem Reaktionsverhalten untersucht [29], [32], [33], so z. B. das p-Chlor-benzylohlorid.…”
Section: Araliphatische Halideunclassified